The mindful resiliency in recovery model: empowering the transcendence of stigma - Moniz-Lewis, David I. K. (Frontiers in Psychology, 2024)
for their ongoing mentorship and for the many conversations that lead to the ideas underlying this manuscript. The primary author would further like to acknowledge that generative artificial intelligence technology was used in the editing of the manuscript. Specifically, Claude 3 Opus and Grammarly AI Writing Assistant were used to edit the manuscript to correct for grammatical and spelling mistakes. At times, Claude 3 Opus was used to provide suggested edits to the authors original writing for improved clarity. All writing presented here is original and derives solely from the primary author.